DRIVING REPURCHASE INTENTION IN E-MARKETPLACES: HOW TRUST MEDIATES THE EFFECTS OF SELLER REPUTATION AND SALES PROMOTION - I Gst. Ngr. Jaya Agung Widagda K.; I Putu Gde Sukaatmadja; Putu Laksmita Dewi Rahmayanti; I Gusti Ayu Tirtayani; Emilia Septiani (Adisam Publisher, 2026)
The purpose of this study was to examine and explain the mediating role of trust in seller reputation and sales promotions on repurchase intention. The study population was an unknown number of consumers using e-marketplaces in Denpasar City. A purposive sampling method was used to select 130 consumers. The analysis technique used was path analysis using SEM-PLS. The results showed that seller reputation and sales promotions had a positive and significant effect on repurchase intention and consumer trust. Trust also had a positive and significant effect on repurchase intention, and trust significantly mediated the partial effect of seller reputation and sales promotions on repurchase intention. Therefore, it is important for e-marketplaces to consistently pay attention to seller reputation and sales promotions to build consumer trust and increase repurchase intention among e-marketplace users in Denpasar City.